Investment in an Islamic Economic Perspective - Yahya , Ibrahim (Islamic Sciences Journal, 2023)
ABSTRACT This research talks about investment, and its importance of in our lives. Islam looks at investment in a holistic and integrated view, as it is one of the foundations of people’s lives. Through it, urbanization is achieved, individuals owned, and societies grow and prosper, in a balanced image that links the world to the hereafter, the individual to the group, and the material to spirit and morals. Investment is one of the legitimate means of earning, as it involves the rotation and volatility of capital, and the harnessing of human and material economic resources. The strength of society and the nation is the strength of their members, and from here, individuals have a great responsibility to increase and enhance money through investment, and in that Sheikh Mahmoud Shaltout says “If among the issues of reason and religion is that what is not done without a duty is an obligation, and the honor of the Islamic group was the first thing that Islam required of its people, and it depended on the three pillars: agriculture, industry, and trade. These pillars were obligatory and their coordination in a manner that achieves the good of the nation was an obligation. ».